2014
DOI: 10.1530/eje-14-0183
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS IN ENDOCRINOLOGY: Regulation of glucose metabolism by the ghrelin system: multiple players and multiple actions

Abstract: Ghrelin is a 28-amino acid peptide secreted mainly from the X/A-like cells of the stomach. Ghrelin is found in circulation in both des-acyl (dAG) and acyl forms (AG). Acylation is catalyzed by the enzyme ghrelin O-acyltransferase (GOAT). AG acts on the GH secretagogue receptor (GHSR) in the CNS to promote feeding and adiposity and also acts on GHSR in the pancreas to inhibit glucose-stimulated insulin secretion. These well-described actions of AG have made it a popular target for obesity and type 2 diabetes me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 116 publications
2
36
1
1
Order By: Relevance
“…These additional parameters will certainly help in evaluating kidney, liver, cardiac, and pancreatic dysfunctions if done at regular intervals of time. Previous studies have shown correlations between ghrelin to both BMI and insulin, However, they did not recommend its routine use of such parameters [11,12]. We have observed higher IR and insulin in T2DM with obesity similar to previously documented [13,14].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These additional parameters will certainly help in evaluating kidney, liver, cardiac, and pancreatic dysfunctions if done at regular intervals of time. Previous studies have shown correlations between ghrelin to both BMI and insulin, However, they did not recommend its routine use of such parameters [11,12]. We have observed higher IR and insulin in T2DM with obesity similar to previously documented [13,14].…”
Section: Discussionsupporting
confidence: 83%
“…Hence, it may play a significant role in DM. Many studies have linked ghrelin to obesity [11,12]. IR is a key factor in metabolic disorders such as hyperglycemia and hyperinsulinemia, which are promoted by obesity and may later lead to T2DM.…”
Section: Homa-β and Dmmentioning
confidence: 99%
“…In addition, it has orexigenic effects (4). Data regarding the regulation and action of UAG are less consistent (5). The ghrelin receptor is also located in peripheral tissues, indicating direct effects of AG (6).…”
Section: Introductionmentioning
confidence: 99%
“…The ghrelin receptor is also located in peripheral tissues, indicating direct effects of AG (6). Among these effects, glucoregulatory properties seem to be important (5) and ghrelin-deficient mice developed profound hypoglycemia during calorie restriction (7). In response to insulin-induced hypoglycemia, however, total (8,9) as well as AG (10) and UAG (11) levels decrease rather than increase in human subjects, irrespective of GH status (12).…”
Section: Introductionmentioning
confidence: 99%
“…The two major ghrelin isoforms appear to have distinct actions and regulate glucose metabolism. The effects of them are still a matter of debate [4]. GLP-1 stimulates postprandial insulin secretion and suppresses glucagon secretion in a glucose-dependent manner, and also slows gastric emptying [5].…”
mentioning
confidence: 99%